BRIQUETTES PRODUCTION FROM LIGNOCELLULOSIC WASTE FOR ENERGY PURPOSES AS AN ALTERNATIVE FUEL - Krinski, I. M.; Mariani, V. C. (Revista de Engenharia Térmica, 2022)
The briquetting process was developed seeking to reuse the waste generated both in forestry production and in industrial processes. The compression of lignocellulosic waste concentrates the available energy in terms of volume and facilitates the handling and storage of these materials. The present work aims to verify the influence on the quality of briquettes of different compositions between the residues of coffee grounds, pine sawdust and cambará sawdust by evaluating the physical, chemical and mechanical characteristics of the briquettes generated from the compaction of these waste. For this, several tests were carried out with the briquettes, analyzing the properties of particle size, resistance to diametrical compression, moisture and ash for each composition of the briquette. The briquettes were produced on a 12-tonne hydraulic press. The waste used showed a high concentration of fine particles, with pine sawdust being 50.5% of particles with a diameter of 0.425mm. Coffee beans have moisture content above 50%, positively impacting the ash content and negatively impacting briquetting and tensile strength by diametral compression. In the production of briquettes, material with up to 60% addition of coffee grounds was obtained. The compression tests showed good results for the treatments, highlighting the treatments with a high concentration of pine. It is also concluded that the coffee grounds can be used in the production of briquettes with sawdust, however, it is suggested for future articles, the correction of moisture in the briquettes for better compaction.